Friday
March 24, 2017

Post a New Question

Posted by on Friday, July 15, 2011 at 11:44pm.

Multiply:
(7x-2)(2x-7)

  • Math - , Friday, July 15, 2011 at 11:51pm

    Hint: use FOIL.

    Here is an example to help you.

    (x + 2)(3x - 4)

    FIRST terms multiplied: x•3x = 3x^2
    OUTER terms multiplied: x(-4) = -4x
    INNER terms multiplied: 2•3x = 6x
    LAST terms multiplied: 2(-4) = -8

    Add them up: 3x^2 - 4x + 6x - 8 = 3x^2 + 2x - 8

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question